PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA (PkM PADA BUMDES DESA TELUK LASONGKO BUTON TENGAH) - Rais R, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
Teluk Lasongko Village, Lakudo District, Central Buton Regency is one of the villages that is trying to develop its potential so that there is income for the village government through BUMDes. The large number of business ventures carried out by BUMDes Teluk Lasongko Village automatically have to provide financial reporting in accordance with the applicable Financial Accounting Standards (SAK ETAP). At this time financial reporting is carried out in accordance with the understanding of its managers which turns out to be not in accordance with the accounting standards it should be. The purpose of this assistance is for partners to understand accounting, which is related to financial reporting in accordance with SAK ETAP. PKM activities are carried out through training methods and also mentoring which are attended by business unit managers, BUMdes supervisors, Working Groups, Fostered MSMEs and Teluk Lasongko Village officials. Participants were very enthusiastic about the explanation and assistance provided by the service team. The output of science and technology achieved is practical knowledge of simple accounting, namely making financial reports in accordance with SAK ETAP.